Changing nature of forced migration : vulnerabilities and responsibilities in South and South-East Asia - Sara N. Amin Varuni Ganepola Lakshman Dissanayake. (ed.); Amin, Sara N.; Ganepola, Varuni; Dissanayake, Lakshman (Dhaka: UPL, 2016)
Protracted conflicts, unequal burden sharing, climate change, globalization, and shifting policies regarding immigration, asylum, work and development are changing the nature of forced displacements and blurring the line between forced migration and economic migration. This book looks at migration dynamics of South and Southeast Asia examining these shifts to contribute to a more interdisciplinary and comprehensive picture of migration for both research and policy-making. We highlight research about migration patterns of groups that are often invisible in the study of migration-women, IPDs, environmental refugees and migrants, South-South migrants, and those that stay behind.
Introduction: Changing Nature of Forced Migration: A Vulnerability Framework -- Part 1: Climate Change, Development and Security. Natural Disasters and Forced Migration: The Case of Tsunami Disaster in Sri Lanka ; Migration Doesn't Have to be a Failure to Adapt: An Escape from Environmental Determinism ; Factors Influencing Environmental Induced Migration in Sanjiangyuan Area in China ; Forced Displacement: A Gendered Analysis of the Tehri Dam Project: Whither Gender? -- Part 2: Legal and Policy Frameworks. Immigration, Global Poverty and the Right to Stay ; Protection without Laws: A Look into the Arbitrariness and Discrimination in Refugee Management in Bangladesh ; International Law, Forced Migrations and the Responsibility to Protect: Examples of Canada, South and South-East Asia ; Vulnerability of Migrants and Responsiveness of the State: The Case of Unskilled Migrant Workers in Kerala, India ; Women's Displacement Experiences: Anthropological Study of Flood IDPs Camp Sukkur, Sindh -- Part 3: Coping Mechanisms. Crisis Coping Strategies in Bangladesh -- Part 4: Politics of Belonging, Settlement, and Identity. A Snapshot Case Study of the Urdu-speaking Internally Displaced Population in Bangladesh ; Partial Citizenship and the Construction of Self via Financial Capital: A Case Study of Legal Bank Account for Illegal Burmese Migrant Workers in Thailand ; Crossing Borders and Shifting Identities: Afghan Women on Move ; Does Religion Facilitate or Impede Migration? A Debate from Gender Perspective in Asia ; Migration as an Adaptation Strategy: Impacts on Urban Integration? A Case Study of Bangladeshi Slums in the Light of Environmentally Induced Migration -- Epilogue: Vulnerabilities and Responsibilities in Forced Migration: Direction for Further Research.
Includes bibliographical references and index.
Keywords: Forced migration -- South Asia; Migration, Internal -- South Asia; Internally displaced persons -- South Asia; Forced migration -- Southeast Asia; Migration, Internal -- Southeast Asia; Internally displaced persons -- Southeast Asia; Forced migration -- Bangladesh; Migration, Internal -- Bangladesh; Internally displaced persons -- Bangladesh